Q: What is the answer to 2s - 3t equals 23 4s plus 3t equals 19?

Write your answer...

Submit

Still have questions?

Continue Learning about Algebra

2s - 12 + 2s = 4s - 124s - 12 = 4s - 124s = 4ss = s==========this is an identity and any number can be s

If p = 2s + 5, then s = (p-5)/2 or 1/2 (p-5) --- p = 2s +5 p-5 = 2s (p-5)/2 = s

2r + 2s = 50 2r - s = 17 therefore 4r - 2s = 34 Add so that you can eliminate one of the variables: 2r + 2s = 50 4r - 2s = 34 ---------------- 6r + 0s = 84 Solve for r: 6r = 84 r = 14 Substitute r into one of the original equations: 2(14) + 2s = 50 28 + 2s = 50 2s = 22 s = 11 Doublecheck with the other original equation: 2(14) - 11 = 28 - 11 = 17

2s + 5 [ge] 49 (ge stands for "greater than or equal to")2s [ge] 44 s [ge] 22 That is, s is greater than or equal to 22.

L = S + 11; 2S + 3(S + 11) = 123, ie 2S + 3S + 33 = 123ie 5S = 90 ie S = 18 and L = 29

Related questions

your answer is 1223

2s-2b= a+b+c-2b simplified that would be a+c-b.

s=4

It is the same as: 2s = t

2s - 12 + 2s = 4s - 124s - 12 = 4s - 124s = 4ss = s==========this is an identity and any number can be s

2s + s + 12 =132 ie 3s = 132 -12 3s = 120 s = 40

3s + 4t + 2s + 5s + 6tGroup all of the like 's' terms & 't' terms together:(3s+2s+5s) + (4t + 6t)10s + 10t or 10(s+t)

2s + 16 = 4s - 6 Subtract 2s from both sides: 16 = 2s - 6 Add 6 to both sides: 22 = 2s divide both sides by 2: s = 11

2s + 17 = 2s + 17 1) First, you want to start on the left side of the equation and subtract 17 from both sides. 2s = 2s 2) Then, you take the 2 on the left side and divide it on both sides. s = s 3) You are left with s (Or 1s) on both sides, so s = 1.

First, add 19 on both sides. You end up with 2s = 48. Then divide both sides by 2 in order to isolate the 's'. You get s = 24.

If p = 2s + 5, then s = (p-5)/2 or 1/2 (p-5) --- p = 2s +5 p-5 = 2s (p-5)/2 = s

2s + s + 12 = 132 3s + 12 = 132 3s = 132 - 12 3s = 120 s = 40